2021
DOI: 10.1108/sajbs-07-2020-0223
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of online buying behavior: a mediation study

Abstract: PurposeThe study is aimed to identify the determinants of online buying behavior and their associations with the consequences of online buying behavior. The study adopted an e-loyalty framework and investigated causal links among functionality, usability, trust, commitment and loyalty. In addition, the study also attempted to investigate the mediating role of trust and commitment between online buying determinants and online purchasing outcomes. The demographic variables of age, gender and income are used as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Further research conducted by Doney and Cannon (1997) and Hsu (2007) strengthened these findings, in which customer loyalty was revealed to be positively affected by trust. Several studies conducted by Jin et al, (2008), Chu (2009), Guenzi et al, (2009), Nguyen et al, (2013), Garepasha et al, (2021) and Bhat et al, (2021) also found that trust had a positive impact on customer loyalty. Similar to the concept of satisfaction, the relationship between trust and loyalty has also become one of the most discussed and popular topics within the realm of marketing research, as it will always be interesting to thoroughly understand how consumers' levels of trust toward a company could eventually affect their loyalty toward the company itself.…”
Section: Impact Of Trust On Customer Loyaltymentioning
confidence: 92%
See 1 more Smart Citation
“…Further research conducted by Doney and Cannon (1997) and Hsu (2007) strengthened these findings, in which customer loyalty was revealed to be positively affected by trust. Several studies conducted by Jin et al, (2008), Chu (2009), Guenzi et al, (2009), Nguyen et al, (2013), Garepasha et al, (2021) and Bhat et al, (2021) also found that trust had a positive impact on customer loyalty. Similar to the concept of satisfaction, the relationship between trust and loyalty has also become one of the most discussed and popular topics within the realm of marketing research, as it will always be interesting to thoroughly understand how consumers' levels of trust toward a company could eventually affect their loyalty toward the company itself.…”
Section: Impact Of Trust On Customer Loyaltymentioning
confidence: 92%
“…Customer loyalty could be defined as the consumers' tendencies and commitments to make another purchasing activity from the same company in the future (Oliver, 1997;Ehigie, 2006;Wilson, 2018). Customer loyalty has long been believed by many people to be an important factor in determining a company's success, not only from the financial perspective, but also in the overall man-ner (Mittal and Lassar, 1998;Duncan and Elliot, 2002;Yap et al, 2012;Wilson et al, 2021;Bhat et al, 2021). Therefore, keeping and retaining customers so that they will not "move away" from the company is an important strategy which every company should do, in order to outperformed their competitors.…”
Section: Customer Loyaltymentioning
confidence: 99%
“…Several researchers while applying TPB have identified various factors that influence consumers' sustainable consumption behaviour and classified these factors into individual-related factors and situational factors [34,14,35,15]. Factors linked to a consumer as an individual include environmental attitude, environmental consciousness, environmental knowledge, green purchasing, recycling behaviour and money availability [36,37] while, situational factors contain innovation, green marketing/ advertising, trust in eco-labelled brands, marketing capabilities, accessibility and availability of ecofriendly brands [38,14,16,39]. Although rigorous efforts have been made to understand consumers' disposition toward environmentally friendly products based of psychological and behavioural determinants [40] however, very few research studies have considered understanding the role of physical attributes such as the preference for retail stores and mode of transportation in securing green purchase intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the COVID-19 outbreak, an online questionnaire survey method was adopted to collect data for the current study [73]. The online survey is considered an effective and acceptable mode for the collection of data [36]. The questionnaire consisted of two sectionssection I captured information related to demographic characteristics viz.…”
Section: Population and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation